Improvement of the Fast ReRoute flow-based model with implementation of the scalable protec-tion schemes of telecommunications network elements - Лемешко, А.В.; Еременко, А.С.; Тарики, Н. (Radiotekhnika, 2016)
The Fast ReRoute flow-based model has been improved, where the node and link protection schemes in the linear form were formulated with the implementation of single path and multipath routing strategies. The use of linear-quadratic optimality criterion was substantiated, and the system hierarchy relations of weight coefficients in the objective function were determined with the aim to ensure maximum network performance and solutions scalability. The efficiency and adequacy of the proposed model of Fast ReRoute were confirmed by a number of numerical examples for solving the single path and multipath routing problems with the implementation of various protection schemes of the network elements.